2018
DOI: 10.19080/jojcs.2018.08.555740
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Metoclopramide Associated with Extrapyramidal Symptoms in a Child: A Case Report

Abstract: Antipsychotics commonly referred to as neuroleptics or major tranquilizers such as butyrophenones, phenothiazine, and thioxanthenes, are commonly used to treat neuropsychiatric disorders and nonneuroleptic agents such as Metoclopramide. The administration of one or both of these drugs can potentially trigger neuroleptic malignant syndrome because of their dopamine receptor-blocking properties [14,15].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Tardive dyskinesia (TD) is a disorder of abnormal muscle movements that is more commonly observed in older individuals with chronic use of DRBAs [1][2][3]. Interestingly, there have been a few cases of acute TD and idiosyncratic drug reactions in young patients using DRBAs [4][5][6]. In one such case report, a 16-year-old male developed TD after two days of oral metoclopramide use [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tardive dyskinesia (TD) is a disorder of abnormal muscle movements that is more commonly observed in older individuals with chronic use of DRBAs [1][2][3]. Interestingly, there have been a few cases of acute TD and idiosyncratic drug reactions in young patients using DRBAs [4][5][6]. In one such case report, a 16-year-old male developed TD after two days of oral metoclopramide use [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the development of TD in patients on chronic metoclopramide for gastroparesis [3]. However, there have only been a few case reports of TD in patients using metoclopramide acutely for nausea and vomiting [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…If metoclopramide is administered, especially intravenously, it must be given slowly over a duration of three minutes or more. The dose of the drug should be limited to less than 0.5 mg per day with a total duration of administration of not more than five days [18].…”
Section: Discussionmentioning
confidence: 99%
“…Sequential reports of complications such as acute dysplasia, Parkinsonism, and delayed dystonia also indicate that metoclopramide can bring about extrapyramidal symptoms and drug-induced motor side effects (15,16). Although metoclopramide causes ocular and pyramidal complications and NMS as a worse form, it is being widely used in clinical practice (17). The onset of this side effect varies following metoclopramide intake, although it occurs more commonly within the first two weeks of consumption.…”
Section: Neuroleptic Malignant Syndrome and Metoclopramidementioning
confidence: 99%
“…Moreover, dantrolene has been positive in treating this syndrome, leading to dramatic and immediate reductions in muscle rigidity and body temperature. The benefits of dantrolene are probably related to its muscle relaxant effects (14,17). It should be noted that drug treatment is not helpful in all cases.…”
Section: Neuroleptic Malignant Syndrome General Management and Clinical Outcomesmentioning
confidence: 99%